Creating mini-pregnancy models in vitro with clinical perspectives - Jee Yoon Park; Hosub Lim; Jianhua Qin; Luke P. Lee (EBioMedicine, 2023)
Summary: During the last decade, organs-on-chips or organoids microphysiological analysis platforms (MAP) have garnered attention in the practical applications of disease models, drug discovery, and developmental biology. Research on pregnant women has firm limitations due to ethical issues; thus, remodelling human pregnancy in vitro is highly beneficial for treatment modality development via disease remodelling or drug monitoring. This review highlights current efforts in bioengineering devices to reproduce human pregnancy and emphasises the significant convergence of biology, engineering, and maternal–foetal medicine. First, we review recent achievements in culturing cells from tissues involved in pregnancy; specifically, trophoblasts from the placenta. Second, we highlight developments in the reconstitution of pregnancy-related female reproductive organs across several structural and functional interpretations. Last, we examine research on the fundamental comprehension of pregnancy-associated diseases to find bioengineering solutions. Recreating human pregnancy through an engineered model is naturally complex; nevertheless, challenges are inevitable to progress precision medicine.